PENERAPAN MODEL PEMBELAJARAN KOPERATIF TIPE GROUPS INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR PEMBELAJARAN IPS SISWA KELAS III SDN 005 BATURIJAL HULU KABUPATEN INDRAGIRI HULU (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2014)
Parameters measured were the result of student learning , mastery learning , studentlearning actvities and teacher activities . Teacher activity during the learning process by usingCooperatife Learning Implementation Model GI Type in the first cycle the first meeting 56.25 %with enough categories , the first cycle of the second meeting of 68.75 % with category Enough. Increased 12.5 % . In the second cycle the first meeting of 84.38 % with a very good category, meeting the second cycle II 90.63 % with very good category 6.25 % increase . Actvities ofstudents during the learning process by using the application of models of gi in the first cycle thefirst meeting of 50.00 % with enough categories , the first cycle of the second meeting of 56.25% with category Enough . 6.25 % increase . In the second cycle the first meeting of 81.25 % witha very good category . In the second cycle the second meeting of 87.50 % with a very goodcategory 6:25 % increase . Cooperatve Learning Model Type Group Investigation in the processof learning can improve student learning outcomes IPS from baseline score ( 45.45 % ) to UH I( 68.18 % ) with increased 22.73 % , the base score ( 45.45 % ) to UH II ( 81.81 % ) increased by36.36 % . Research in Public Elementary School three grade 001 Baturijal Hulu prove that theimplementation of cooperative learning model to improve learning outcomes GI IPS grade IIIElementary School 001 Baturijal Hulu District of Indragiri HuluKeyword : Model Learning GI, Students Achievement